Making the Unwanted Visible: A Narrative on Abdülhamid Ii’s Ambitious Project for Yedikule Central Prison in Istanbul - Ceren Katipoğlu Özmen; Selahaddin Sezer (Prostor, 2020)
This study aims to investigate three architectural projects proposed for constructing a central prison inside the Yedikule Fortress in Istanbul during the end of the 19th c. Ottoman State assigned the famous architects of the era for this mission such as August Jasmund, Alexandre Vallaury, and Kemaleddin. The narration on the projects shows that there was a strong intention for constructing a central prison in the capital of Ottoman Empire as a sign of success for the overall penalty and prison reform that was one of the main goals for Ottoman Sultan Abdülhamid II (r. 1876-1909). The interpretation of these distinctive projects is significant since this interpretation helps us both to understand the transformation of the criminal justice spaces of the Ottoman Empire and to provide a new perspective for reading 19th c. Ottoman architecture.